Solution-based synthesis of high yield CZTS (Cu2ZnSnS4) spherical quantum dots. (January 2015) - Rajesh, G.; Muthukumarasamy, N.; Subramanian, E.P.; Venkatraman, M.R.; Agilan, S.; Ragavendran, V.; Thambidurai, M.; Velumani, S.; Yi, Junsin; Velauthapillai, Dhayalan
Graphical abstract: Schematic diagram of CZTS quantum dots Highlights: Novel CZTS quantum dots has been synthesized by simple chemical precipitation technique. High yield CZTS quantum dots were obtained at 170  ° C. The optical band gap is shifted to the higher energy side and it shows the presence of quantum confinement effect. Abstract: High yield CZTS quantum dots have been synthesized using simple precursors by chemical precipitation technique. Formation mechanism of CZTS spherical quantum dots also has been investigated. According to the mechanism, copper sulfide nuclei firstly forms, and serves as the starting point for the nucleation and growth of CZTS. X-ray diffraction pattern, X-ray photoelectron spectra (XPS) and Raman spectra reveals the formation of pure kesterite structure Cu2 ZnSnS4 nanoparticles. HRTEM analysis reveals the formation of CZTS quantum dots with an average particle size of ∼8.3 nm. The elemental distribution of CZTS quantum dots studied using STEM elemental mapping reveals that Cu, Zn, Sn and S are present in the sample. The photoluminescence spectra of CZTS exhibit a broad red emission band at 657 nm. The optical band gap is shifted to the higher energy side and it shows the presence of quantum confinement effect.